The Effect of Compensation and Job Satisfaction on Employee Performance through Work Motivation as an Intervening Variable at CV. Pendawa Kencana Multifarm in Yogyakarta - Radityo Kenny Wardhana; Andriyastuti Suratman (Penerbit Jurnal Indonesia, 2026)
This study aims to examine the effect of compensation policy and job satisfaction on employee performance, with work motivation as a mediating variable, at CV. Pendawa Kencana Multifarm in Yogyakarta. Compensation and job satisfaction that are not managed fairly and transparently risk lowering motivation and performance among employees in the agricultural sector, which demands high productivity. This study employed a quantitative approach using a survey method, distributing questionnaires to 156 employees selected through purposive sampling. Data were analyzed using Structural Equation Modeling-Partial Least Squares (SEM-PLS) with the assistance of SmartPLS software, covering the evaluation of the outer model (validity and reliability) and the inner model (coefficient of determination and hypothesis testing). The results show that compensation policy and job satisfaction each have a positive and significant effect on both work motivation and employee performance, and that work motivation has a positive and significant effect on employee performance. Work motivation was also found to mediate the effect of compensation policy and job satisfaction on employee performance. These findings indicate that improving employee performance depends not only on compensation and job satisfaction directly, but also on strengthening work motivation as a mediating mechanism. The implication is that CV. Pendawa Kencana Multifarm needs to develop a fair and transparent compensation system, improve job satisfaction through a supportive work environment, and strengthen work motivation to drive sustainable employee performance. Specifically, compensation policy and job satisfaction jointly explained 45.2% of the variance in work motivation (R² = 0.452) and, together with work motivation, explained 61.8% of the variance in employee performance (R² = 0.618). All seven hypothesized paths were statistically significant (T-statistics 2.390-6.117; p ≤ 0.017), including the indirect (mediating) effects of compensation policy (β = 0.146; p = 0.004) and job satisfaction (β = 0.210; p < 0.001) on employee performance through work motivation.